2019
DOI: 10.1051/e3sconf/20197903021
|View full text |Cite
|
Sign up to set email alerts
|

A study on heavy metal sorption properties of intestinal microbiota in vitro

Abstract: Water and soil pollution by heavy metals has led to their accumulation in the ground and waters, to a sharp decline of ecosystem biopotential, and to foodstuff contamination, resulting in internal pollutions in bodies of humans and animals with food, air, water. In this regard, the purpose of our study was to examine the impact of heavy metals on the growth of representatives of rats’ intestinal microbiota and to estimate sorption characteristics of these microorganisms. The research was conducted in three sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…There were no consistent results about microbiota changes in each study at the taxa level of species, genus, family, order, or even phylum, which may result from differences in dosage of the heavy metals, exposure time, physiological feature of experimental animals, and most importantly, the food composition of the diet (Tinkov et al, 2018). Anyhow, different intestinal microbes responded differently to heavy metal stresses, and their maximum tolerated concentrations and sorption properties were different (Riley and Mee, 1982;Sizentsov et al, 2019). Our in vivo experiments in mice showed that under 100 ppm As, Cd, or Pb, most gut microbes were tolerant without abundance change while a few were sensitive indicated by a decrease in abundance ( Supplementary Figures S2-S7 and Supplementary Table S2), implying that some intestinal microbes might not respond to stresses from specific heavy metals.…”
Section: Discussionmentioning
confidence: 94%
“…There were no consistent results about microbiota changes in each study at the taxa level of species, genus, family, order, or even phylum, which may result from differences in dosage of the heavy metals, exposure time, physiological feature of experimental animals, and most importantly, the food composition of the diet (Tinkov et al, 2018). Anyhow, different intestinal microbes responded differently to heavy metal stresses, and their maximum tolerated concentrations and sorption properties were different (Riley and Mee, 1982;Sizentsov et al, 2019). Our in vivo experiments in mice showed that under 100 ppm As, Cd, or Pb, most gut microbes were tolerant without abundance change while a few were sensitive indicated by a decrease in abundance ( Supplementary Figures S2-S7 and Supplementary Table S2), implying that some intestinal microbes might not respond to stresses from specific heavy metals.…”
Section: Discussionmentioning
confidence: 94%
“…One way to detect these disorders is to intravitally diagnose metabolic disorders with the help of morphological and biochemical E3S Web of Conferences 164, 06020 (2020) TPACEE-2019 https://doi.org/10.1051/e3sconf /202016406020 blood indicators. These studies are particularly important in assessing the effects of new fodder substances [5][6][7].…”
Section: Morphological and Biochemical Blood Indicatorsmentioning
confidence: 99%
“…This waste is a good source of valuable protein, since it is inferior to animal protein only in the content of lysine. The only drawback of such feeds, and particularly of sunflower one, is the significant content of crude fiber due to husk [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical approaches are available to restore metals, but they are often expensive to use and do not have the specificity necessary to process target metals against the background of competing ions. In addition, such approaches are not applicable to the cost-effective recovery of large-scale underground pollution on the spot [1,2].…”
Section: Introductionmentioning
confidence: 99%